The predictive value of the prognostic staging system in the 8th edition of the American Joint Committee on Cancer for triple-negative breast cancer: a SEER population-based analysis. (8th January 2019) - Liu, Ying-Ying; Yu, Tian-Jian; Liu, Guang-Yu
Aim: To examine the stage changes and survival differences among triple-negative breast cancer (TNBC) patients based on the prognostic staging system.Methods: We used the SEER database to identify eligible patients with TNBC diagnosed between 2010 and 2014. Kaplan–Meier curves were drawn for comparison. The primary end point was breast cancer-specific survival.Results: The median follow-up time was 26 months for 19, 608 patients. The stages of all TNBC patients increased or remained unchanged during rearrangement from anatomic staging to prognostic staging. Stage IIA, IIIA and IIIC comprised the majority of patients. Several patients did not have prognostic staging. Stage IIIC incorporated six substages that contributed to high heterogeneity. Overall, the Kaplan–Meier curves still showed the favorable differentiation among stages and substages, with the exception of stage IIB and substage IIIA (T2N0, grade 2–3) patients.Conclusion: The prognostic information for breast cancer patients provided by the novel prognostic staging system may be less accurate for TNBC patients in our independent analysis. Moreover, stage IIB and substage IIIA (T2N0, grade 2–3) should possibly undergo further evaluation.